2003
DOI: 10.1038/ng1281
|View full text |Cite
|
Sign up to set email alerts
|

Growth and specification of the eye are controlled independently by Eyegone and Eyeless in Drosophila melanogaster

Abstract: Control of growth determines the size and shape of organs. Localized signals known as 'organizers' and members of the Pax family of proto-oncogenes are both elements in this control. Pax proteins have a conserved DNA-binding paired domain, which is presumed to be essential for their oncogenic activity. We present evidence that the organizing signal Notch does not promote growth in eyes of D. melanogaster through either Eyeless (Ey) or Twin of eyeless (Toy), the two Pax6 transcription factors. Instead, it acts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
164
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(169 citation statements)
references
References 47 publications
5
164
0
Order By: Relevance
“…Similarly, in mice, homozygous mutations of the Pax6 homologue small eye (sey) lead to a distinct phenotype with early postnatal death and absence of eyes whereas heterozygous (sey/ þ ) mutations show microphthalmia and corneal, chamber angle and lenticular abnormalities 16,17 with striking similarities to the human condition. 5,8,15,18 There is growing evidence that the two major isoforms of PAX6, PAX6( þ 5a) and PAX6(À5a) may play different biological roles: Dominguez et al 19 have shown lately that in fDrosophila PAX6( þ 5a) functions primarily in the regulation of growth and less effectively in eye specification than Pax6(À5a). Furthermore, the Pax6( þ 5a) isoform is involved in the chain of events leading to formation of the fovea centralis in the developing chick eye whereas Pax6(À5a) is not.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in mice, homozygous mutations of the Pax6 homologue small eye (sey) lead to a distinct phenotype with early postnatal death and absence of eyes whereas heterozygous (sey/ þ ) mutations show microphthalmia and corneal, chamber angle and lenticular abnormalities 16,17 with striking similarities to the human condition. 5,8,15,18 There is growing evidence that the two major isoforms of PAX6, PAX6( þ 5a) and PAX6(À5a) may play different biological roles: Dominguez et al 19 have shown lately that in fDrosophila PAX6( þ 5a) functions primarily in the regulation of growth and less effectively in eye specification than Pax6(À5a). Furthermore, the Pax6( þ 5a) isoform is involved in the chain of events leading to formation of the fovea centralis in the developing chick eye whereas Pax6(À5a) is not.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this model, the lack of eye development in mutants for eyegone, a target of Notch signaling that is required for disc growth (33), can be rescued by inhibiting Wg signaling in posterior cells (34). In the third instar eye disc, wg expression is restricted to the anterior lateral margins (6,13,15,29,35), where it continues to repress the expression of Eya, So and Dac in regions destined to form the dorsal head (30).…”
Section: Wg Inhibits Eye Specificationmentioning
confidence: 83%
“…Drosophila eye development is regulated by several Pax6 homologs (eyeless, eyegone, twin-ofeyeless, and twin-of-eyegone) (18) that function in synchrony with eyes absent, sine oculus (so or six), and dachshund (Dach) proteins (54). Conservation of this pathway by paralogous genes has been observed in murine myogenesis, where Pax3 and Eya2 function upstream of myogenic regulatory factors to induce myogenesis (60).…”
Section: Discussionmentioning
confidence: 99%
“…Full-length cDNAs encoding alternate isoforms of Pax7 (a-d) were isolated via nested RT-PCR from RNA of C57BL/6J mouse gastrocnemius muscle. RNA (1.8 g) was reverse transcribed using Omniscript reverse transcriptase (Qiagen) and oligo-dT 18 primers in a 20 l standard reaction. cDNA solution (2 l) was PCR amplified in a 25 l reaction using ProofStart DNA polymerase (Qiagen) for 35 cycles of 3-step PCR with primers F1 (5Ј-GAGGTTTATCCAGCCGACTCTGG-3Ј) and R1 (5Ј-AGGGTTGGCTGGGCCACTGGATGG-3Ј), with an annealing temperature of 55°C and 2 min extension times.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation